The impact of the European Union fiscal rules on economic growth - Castro, Vítor (2011)
This paper analyses whether Maastricht and Stability and Growth Pact fiscal rules have affected growth in the European Union negatively. A growth equation is specified for a group of 15 European Union countries (and 8 OECD countries) over the period 1970–2005 to analyse this issue. Panel estimations using fixed-effects, pooled mean group and system-GMMestimators show that the institutional changes that occurred in the European Union after 1992 were not harmful to growth. Moreover, results show that growth is slightly higher in the period in which the fulfilment of the 3% criteria for the deficit started to be officially assessed, i.e. after 1997